2006
DOI: 10.1097/01.bpo.0000242429.83866.97
|View full text |Cite
|
Sign up to set email alerts
|

Bifocal Tibial Corrective Osteotomy With Lengthening in Achondroplasia

Abstract: The results and complications of bifocal tibial osteotomies with gradual correction and lengthening by Ilizarov ring fixator performed in 47 tibiae in 24 achondroplastic patients were analyzed. Comparison was made between the parameters of angular and torsional deformities of the tibia preoperatively, at fixator removal, and at last follow-up. Of these parameters, statistically significant change was seen postoperatively in the values of medial proximal tibial angle, lateral distal tibial angle, mechanical axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 18 publications
1
28
2
1
Order By: Relevance
“…Achondroplasia is the most frequently encountered form of nonlethal skeletal dysplasia [4] and is characterized by defective enchondral ossification owing to defective gene encoding for fibroblast growth factor receptor 3 [6,14,20]. It is a type of rhizomelic dwarfism with an incidence of approximately one in 10,000 live births [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achondroplasia is the most frequently encountered form of nonlethal skeletal dysplasia [4] and is characterized by defective enchondral ossification owing to defective gene encoding for fibroblast growth factor receptor 3 [6,14,20]. It is a type of rhizomelic dwarfism with an incidence of approximately one in 10,000 live births [6].…”
Section: Introductionmentioning
confidence: 99%
“…Limb lengthening by the Ilizarov method has been used in patients with achondroplasia by many authors during the past few decades, but with varying amounts of success [2,3,6,8,13,16,18,20]. Cattaneo et al [6] reported a considerable increase in length (14-18 cm) without major risk.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the condition requires realignment surgery with a goal of limb alignment correction or limb lengthening [11,18,20]. The hip and knee alignment in achondroplastic children has been analyzed by Inan et al [7,8]; however, the foot and ankle alignment in achondroplastic children is less well understood and easy to be overlooked [5].…”
Section: Discussionmentioning
confidence: 99%
“…These measurements are important in evaluating the hindfoot, midfoot, and forefoot deformities. Surgical planning should focus not only on the lower limb alignment [11,20], but also on the complex deformities of the foot and ankle. Further research will apply these radiographic measurements to a series of affected feet in patients who have undergone operations for axial deviations to confirm whether these measurement methods of ''virgin'' feet are equally valid in postoperative patients with ACH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation